Insight stories: Looking into teacher support in enhancing scientific thinking skills among pre-school students - Monnas, Latifah Binti (FKIP-Universitas Riau, 2018)
Due to the revision of the National Pre-School StandardCurriculum (KSPK) 2017, the strengthening of Science and TechnologySupport and STEM integration early childhood education in Malaysia isnow being aggressively developed in line with national education policies.This case study is conducted to find out how pre-school teachers applyscience process elements in their teaching and learning activities.Observation was carried out on a pre-school teacher during a lesson in oneof the national pre-schools in Tawau. Observation findings show that preschoolteachersunderstandtheneedforearlyscienceeducationthoughtheylackthe knowledge and application of the scientific skills. Therefore, it ishighly recommended for pre-school teachers to improve appropriatepedagogical practices, and support the early process of science in earlychildhood education by contextually emphasizing and linking their teachingto the 21st century curriculum.